2005
DOI: 10.3852/mycologia.97.4.793
|View full text |Cite
|
Sign up to set email alerts
|

Heterothallic mating observed between Mexican isolates of Glomerella lindemuthiana

Abstract: Although several reports have described the occurrence of the teleomorphic state of Glomerella lindemuthiana (anamorph, Colletotrichum lindemuthianum), there has been a lack of continuity in this research. To identify G. lindemuthiana isolates capable of developing the teleomorphic state, 19 Mexican isolates were analyzed. Three types of response were observed: (i) negative, where only mycelial growth with or without acervuli was observed; (ii) potential, where in addition to the above, spherical perithecia-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…These experiments, performed by multiple laboratories, focused on detection of the highly conserved alpha DNA binding domain that characterizes the Mat1-1 idiomorph in other ascomycete fungi. None of these approaches provided any evidence for the presence of a Mat1-1 gene, even from homothallic strains of Colletotrichum (Crouch et al 2006;Du et al 2005, Rodríguez-Guerra et al 2005García-Serrano et al 2008). BLAST searches of the four Colletotrichum genome sequences confirmed the absence of any sequence with significant identity to the Mat1-1 gene.…”
Section: Mating Type Genesmentioning
confidence: 96%
See 1 more Smart Citation
“…These experiments, performed by multiple laboratories, focused on detection of the highly conserved alpha DNA binding domain that characterizes the Mat1-1 idiomorph in other ascomycete fungi. None of these approaches provided any evidence for the presence of a Mat1-1 gene, even from homothallic strains of Colletotrichum (Crouch et al 2006;Du et al 2005, Rodríguez-Guerra et al 2005García-Serrano et al 2008). BLAST searches of the four Colletotrichum genome sequences confirmed the absence of any sequence with significant identity to the Mat1-1 gene.…”
Section: Mating Type Genesmentioning
confidence: 96%
“…Colletotrichum does not conform to this system. To date, only the Mat1-2 idiomorph, with the characteristic conserved high mobility group (HMG) binding domain, is known from any Colletotrichum species surveyed, regardless of whether the strains are heterothallic or homothallic (Crouch et al 2006;Du et al 2005, Rodríguez-Guerra et al (2005; García-Serrano et al (2008); Vaillancourt et al 2000b). However, genetic evidence does point to at least two unlinked loci acting as mating determinants in crosses involving C. graminicola strains M1.001 and M5.001 (Vaillancourt et al 2000a).…”
Section: Mating Type Genesmentioning
confidence: 99%
“…phaseoli . During the past 20 years, a number of genetic studies using morphological and molecular markers have demonstrated the formation of recombinant forms during the sexual phase (Batista and Chaves, 1982; Bryson, 1990; Mendes‐Costa, 1996; Rodriguez‐Guerra et al., 2005; Camargo et al., 2007; Luna‐Martinez et al., 2007), results which may explain the remarkable variability that has been observed amongst different populations of the fungus (Rodriguez‐Guerra et al., 2005; Camargo et al., 2007). The meiospore producing form of the ascomycete has been observed in field‐collected isolates maintained under laboratory conditions in the absence of artificial inducers (Camargo et al., 2007; Damasceno e Silva et al., 2007; Souza et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The Gibberella fujikuroi species complex counts at least eight different heterothallic species pathogenic on pine, maize, rice, banana in both temperate and tropical conditions, with massive socio-economic effects (Steenkamp et al, 2000;Nirenberg and O'Donnell, 1998). Colletotrichum lindemuthianum, responsible for black spot disease of common bean, is considered heterothallic as well as many strains in the Colletotrichum genus (Rodríguez-Guerra et al, 2005;Cannon et al, 2012). More generally, with the advent of genomes studies, more and more species once classified as asexual, are now recognized as having retained the machinery for sexual reproduction and in some cases as having operational heterothallism genes (Ene and Bennett, 2014).…”
Section: Introductionmentioning
confidence: 99%